Buffer Overflow Vulnerability Detection Based on Unsafe Function Invocation. (June 2020) - Zhao, Xianda; Huang, Shuguang; Pan, Zulie; Hui, Huang
Abstract: Buffer overflow vulnerabilities are widespread in software programs and pose a serious security threat. In order to effectively mitigate buffer vulnerabilities, we proposed a buffer overflow vulnerability detection technique based on unsafe function invocation. By extracting the typical characteristics of the insecure function call operation, a vulnerability code characteristic model is constructed, and the model is used as a guide to use the data flow analysis method for vulnerability detection. Experimental results show that our method can effectively detect buffer overflow problems caused by unsafe function invocation in programs.